Late presentation of Nipah virus encephalitis and kinetics of the humoral immune response. Issue 4 (1st October 2001) - Wong, S C; Ooi, M H; Wong, M N L; Tio, P H; Solomon, T; Cardosa, M J
Abstract : Nipah virus is a newly discovered paramyxovirus transmitted directly from pigs to humans. During a large encephalitis outbreak in Malaysia and Singapore in 1998–9, most patients presented acutely. A 12 year old child is described who developed encephalitis 4 months after exposure to the virus. She was diagnosed by a new indirect IgG enzyme linked immunosorbent assay (ELISA), which is also described. The late presentation and IgG subclass responses had similarities to subacute sclerosing panencephalitis. Nipah virus should be considered in patients with encephalitis even months after their possible exposure.